2001
DOI: 10.1037/0022-3514.81.5.946
|View full text |Cite
|
Sign up to set email alerts
|

Implementation intentions and efficient action initiation.

Abstract: Implementation intentions ("If I encounter Situation X, then I'll perform Behavior Y!") are postulated to instigate automatic action initiation (P. M. Gollwitzer, 1993Gollwitzer, , 1999. In 4 studies, the hypothesis was tested that implementation intentions lead to immediate action initiation once the specified situation is encountered, even under conditions of high cognitive load. First, individuals whose action control is known to be hampered by disruptive cognitive business, such as opiate addicts under wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
393
4
11

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 467 publications
(434 citation statements)
references
References 45 publications
26
393
4
11
Order By: Relevance
“…The studies that have focused on implementation intention mechanisms have been conducted in the laboratory (e.g., Aarts et al, 1999;Webb & Sheeran, 2007) and thus the generalizability within more real-life settings is not clear. If implementation intentions do increase the accessibility of the planned situation and the link between the stimulus and response to the point that it reflects features of automaticity such as immediacy and efficiency (e.g., Brandstätter, Lengfelder, & Gollwitzer, 1997) then people should consistently respond in the same way when encountering the same situational cues. Consequently, recall of their plans should be sound.…”
Section: Discussionmentioning
confidence: 99%
“…The studies that have focused on implementation intention mechanisms have been conducted in the laboratory (e.g., Aarts et al, 1999;Webb & Sheeran, 2007) and thus the generalizability within more real-life settings is not clear. If implementation intentions do increase the accessibility of the planned situation and the link between the stimulus and response to the point that it reflects features of automaticity such as immediacy and efficiency (e.g., Brandstätter, Lengfelder, & Gollwitzer, 1997) then people should consistently respond in the same way when encountering the same situational cues. Consequently, recall of their plans should be sound.…”
Section: Discussionmentioning
confidence: 99%
“…Setting implementation plans are effective at increasing the consistency between goal-directed intentions and behavior by increasing behavioral automaticity. The mechanism connects an environmental cue with the goal intention, making associations between the behavior and the cue more accessible in memory (Brandstätter, Lengfelder, & Gollwitzer, 2001). Stewart and Payne's (2008) implementation intentions manipulation was adapted for the present intervention.…”
Section: Intentional Strategies To Overcome Biasesmentioning
confidence: 99%
“…Gollwitzer and his colleagues (Brandstätter et al, 2001;Gollwitzer, 1999;Gollwitzer & Brandstätter, 1997) provided important evidence of the transfer from conscious direction to automatic execution. Many studies have shown that forming an implementation intention facilitates behavior and removes the need for further, conscious efforts (e.g., Gollwitzer, 1993).…”
Section: Automatizationmentioning
confidence: 99%
“…Formulating such a plan creates a link between the anticipated cue (X) and the desired behavior (Y). As a result, perception of the cue causes the behavior to be executed automatically and without conscious guidance (Brandstätter, Lengfelder, & Gollwitzer, 2001). In essence, the conscious plan reprograms the automatic response.…”
Section: From Simulation To Actionmentioning
confidence: 99%